PENGARUH PERILAKU PETANI TERHADAP RISIKO KEEFISIENAN USAHATANI KENTANG DI KABUPATEN WONOSOBO JAWA TENGAH - Anny Hartati (Agroland: Jurnal Ilmu-ilmu Pertanian, 2007)
Research using survey method was carried out at Wonosobo Regency with collected sample size of 87 farmers.Utility function, gross margin (as time function), and regression analyses with degrees function were used. Result of theresearch showed that all of farmers could handle their potato farming risk. Cost and average revenue per hectare could bepredicted by using three degrees polynomial function appropriately. Economics social factor, age, education, numbers offamily, farm experience, land wide and occupied field status significantly affected farmer behavior risk to conduct their potatofarming. The higher the age, the education, the numbers of family, the farm experience, the land wide, and the status, thehigher the farmer bravery to handle the risk.Keywords: Behavior, risk, and efficiency.